Conceptual design and comparative stiffness analysis of an Exechon-like parallel kinematic machine with lockable spherical joints. (16th August 2017) - Tang, Teng-fei; Zhang, Jun
This article proposes two types of lockable spherical joints which can perform three different motion patters by locking or unlocking corresponding rotational axes. Based on the proposed lockable spherical joints, a general reconfigurable limb structure with two passive joints is designed with which the conceptual designs of two types of Exechon-like parallel kinematic machines are completed. To evaluate the stiffness of the proposed Exechon-like parallel kinematic machines, an expanded kinetostatic model is established by including the compliances of all joints and limb structures. The prediction accuracy of the expanded stiffness model is validated by numerical simulations. The comparative stiffness analyses prove that the Exe-Variant parallel kinematic machine claims competitive rigidity performance to the Exechon parallel kinematic machine. The present work can provide useful information for further investigations on structural enhancement, rigidity improvement, and dynamic analyses of other Exechon-like parallel kinematic machines.